Impact of Direct Endoscopic Necrosectomy on Recurrence of Symptoms or Fluid Collections Following Successful Endoscopic Transmural Drainage of Walled-off Necrosis in Disconnected Pancreatic Duct - Rana, Surinder Singh; Bush, Nikhil; Sharma, Ravi; Gupta, Rajesh (Journal of Digestive Endoscopy, 2023)
Background The impact of direct endoscopic necrosectomy (DEN) on risk of recurrence of symptoms or pancreatic fluid collections (PFCs) in patients with disconnected pancreatic duct (DPD) has not been previously evaluated.Objective To compare the risk of recurrence of PFC in patients with walled-off necrosis (WON) and DPD undergoing DEN with that of not requiring DEN and not having permanent indwelling plastic stents.Methods Retrospective analysis of database of patients with WON successfully treated with transmural metal stents over the past 5 years was done to identify patients with DPD and not having permanent indwelling transmural stents. These patients were divided into two groups: Group A: patients undergoing DEN and Group B: patients not requiring DEN.Results Seventeen patients required DEN (Group A; mean age 37.8 years) and 21 patients were successfully treated without DEN (Group B; mean age: 37.7 years). In Group A, none of the patients developed either recurrence of symptoms or PFC over a mean follow-up period of 7 months. In Group B, 5 of 21 (23.8%) patients developed either recurrence of pain (n = 2) or PFC (n = 3) over a mean follow-up period of 22 months. New-onset diabetes mellitus developed in five (29%) patients in Group A and two (9%) patients in Group B. None of the patients in either group developed steatorrhea.Conclusion Patients with WON and DPD treated with lumen apposing metal stent and requiring DEN seem to be having low risk of developing recurrence of pain or PFC.
Keywords: endoscopic ultrasound; pancreatitis; lumen apposing metal stents; walled-off necrosis